2020
DOI: 10.26804/ager.2020.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of shale image based on Wasserstein Generative Adversarial Networks with gradient penalty

Abstract: Generative Adversarial Networks (GANs), as most popular artificial intelligence models in the current image generation field, have excellent image generation capabilities. Based on Wasserstein GANs with gradient penalty, this paper proposes a novel digital core reconstruction method. First, a convolutional neural network is used as a generative network to learn the distribution of real shale samples, and then a convolutional neural network is constructed as a discriminative network to distinguish reconstructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Given massive data, it can extract rich and comprehensive effective information, and then use them to classify and predict. At the same time, it can accurately get the weight of each influencing factor, so as to reflect the actual problems in a more real way [27,28].…”
Section: Construction Of Comprehensive Decision Indexmentioning
confidence: 99%
“…Given massive data, it can extract rich and comprehensive effective information, and then use them to classify and predict. At the same time, it can accurately get the weight of each influencing factor, so as to reflect the actual problems in a more real way [27,28].…”
Section: Construction Of Comprehensive Decision Indexmentioning
confidence: 99%
“…On top of GANs, Shams et al (2020) integrated it with auto-encoder networks to produce sandstone samples with multiscale pores, enabling GANs to predict inter-grain pores while auto-encoder networks provide GANs with intragrain pores. Some other representative applications also exist, such as adopting GANs to reconstruct shale digital cores (Zha et al 2020), utilizing GANs to augment resolution and recover the texture of micro-CT images of rocks (Wang et al 2019(Wang et al , 2020, and reconstructing three-dimension structures from two-dimension slices with GANs (Feng et al 2020;Kench and Cooper 2021;You et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Valsecchi et al used DCGANs to generate 3D digital cores from 2D images of rocks, which is fast and accurate [37]. Zha et al used WG-GANs to generate high-quality shale pictures, which are consistent and diverse with real shale samples [38]. Feng et al used CGANs to obtain a complete core image from a limited image [39].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that high-quality digital core models can be obtained by using network models that generative adversarial neural networks and its variants. 3 Geofluids However, the training of GANs is a complicated process, and it is easy to encounter problems such as gradient disappearance or mode collapse during the training process [38]; it usually takes thousands or even tens of thousands of training times to achieve a better generation effect. Therefore, it is of great significance to find a way to effectively reduce the number of trainings of GANs.…”
Section: Introductionmentioning
confidence: 99%